2007
DOI: 10.1007/s00520-007-0278-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning of young adolescent and adult survivors of childhood cancer

Abstract: The long-term psychological functioning of Greek survivors of childhood cancer is satisfactory, with emotional difficulties, such as increased anxiety and lower self-esteem, receding over time. Survivors experience personal growth and mature through trauma as they develop a positive view of the impact that the cancer experience has upon their life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 31 publications
4
42
2
3
Order By: Relevance
“…Consistent with previous research (Boman and Bodegård, 2004;Brown et al, 2008;Eiser et al, 1997;FelderPuig et al, 1998;Gerber et al, 2006;Gerhardt et al, 2007;Servitzoglou et al, 2008), survivors of our study also perceived cancer as an obstacle in the making of their educational plans. Our study emphasizes the role of immediate and medium-term objective effects of cancer on these feelings of work limitations, as most of the survivors reporting cancer as an obstacle had to face the physical sequelae of cancer before they reached the age of 20, often because of retinoblastoma or osteosarcoma, cancers that could both lead to amputation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous research (Boman and Bodegård, 2004;Brown et al, 2008;Eiser et al, 1997;FelderPuig et al, 1998;Gerber et al, 2006;Gerhardt et al, 2007;Servitzoglou et al, 2008), survivors of our study also perceived cancer as an obstacle in the making of their educational plans. Our study emphasizes the role of immediate and medium-term objective effects of cancer on these feelings of work limitations, as most of the survivors reporting cancer as an obstacle had to face the physical sequelae of cancer before they reached the age of 20, often because of retinoblastoma or osteosarcoma, cancers that could both lead to amputation.…”
Section: Discussionsupporting
confidence: 93%
“…They showed that young survivors could report a negative impact of cancer on their vocational aspirations (Badell et al, 1998;Gerber et al, 2006;Servitzoglou et al, 2008), lower professional expectations or less concrete plans for the future (Boman and Bodegård, 2004;Gerhardt et al, 2007;Servitzoglou et al, 2008), or a change in their career plans resulting from cancer (Felder-Puig et al, 1998;Servitzoglou et al, 2008). However, most of these studies were conducted during the transition from adolescence to emerging adulthood, with young survivors who had not necessarily completed their education, lacking perspective in their career and in their life course.…”
Section: Introductionmentioning
confidence: 97%
“…A last study found that the full-time employment of childhood cancer survivors was lower than national norms (US), except among survivors of hematologic malignancies who had not received radiation therapy [18]. A part of explanation of our result could be that these young adults who survived childhood AL might be particularly motivated to work and accept a job, even unstable, when their health allows [42]. Another explanation could be that employers would be more reluctant to give cancer survivors a permanent contract.…”
Section: Discussioncontrasting
confidence: 53%
“…It has good construct and content validity and has been successfully used in older cancer patients and AYA survivors of childhood cancer [26][27][28]. It also has excellent reliability in adolescents with cancer, with a Cronbach's alpha of 0.89 [9].…”
Section: State-trait Anxiety Inventory Form Ymentioning
confidence: 99%